Corruption, Exchange Rates, and Migration Flows - Agiomirgianakis, George; Bertsatos, Georgios; Sfakianakis, George (Review of Economic Analysis, 2024)
It is often argued that immigration flows depend positively upon the GDP (a migratory pull factor) and negatively upon the exchange rate depreciations (a migratory push factor) in the destination country. However, we show that both effects depend crucially on the corruption level, and, to the best of our knowledge, this is the first time that the impact of migration’s determinants depends on the level of corruption and therefore, migratory flows are found to be corruption dependent. In fact, we show that high corruption in the destination country could lead to a decoupling of the net migration flows from both effects (GDP and PPP exchange rate). The policy implications of our findings suggest that corruption, and its interactions with other migration factors, should in principle be examined in migration studies. We employ net migration flows, defined as immigrants minus emigrants, for the case of Greece as destination country where migration-flows direction has changed sign two times in the post-war era. The data are obtained from the World Bank. Our findings remain robust [1] to a series of alternative specifications with the world governance indicators (WGIs) and, [2] to the use of several estimators.